2022
DOI: 10.18632/aging.203992
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of action of triptolide against colorectal cancer: insights from proteomic and phosphoproteomic analyses

Abstract: Triptolide is a potent anti-inflammatory agent that also possesses anticancer activity, including against colorectal cancer (CRC), one of the most frequent cancers around the world. In order to clarify how triptolide may be effective against CRC, we analyzed the proteome and phosphoproteome of CRC cell line HCT116 after incubation for 48 h with the drug (40 nM) or vehicle. Tandem mass tagging led to the identification of 403 proteins whose levels increased and 559 whose levels decreased in the presence of trip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 52 publications
(48 reference statements)
0
8
0
Order By: Relevance
“…Accumulating evidences revealed that triptolide has a strong antitumor effect in a broad range of cancers, including non-small cell lung cancer (Zhou et al, 2022c), colorectal cancer (Liskova et al, 2022;Song et al, 2022), hepatocellular carcinoma (Li et al, 2022b), acute myeloid leukemia (Chen et al, 2022b;Kang et al, 2022b) and so on.…”
Section: Triptolidementioning
confidence: 99%
See 1 more Smart Citation
“…Accumulating evidences revealed that triptolide has a strong antitumor effect in a broad range of cancers, including non-small cell lung cancer (Zhou et al, 2022c), colorectal cancer (Liskova et al, 2022;Song et al, 2022), hepatocellular carcinoma (Li et al, 2022b), acute myeloid leukemia (Chen et al, 2022b;Kang et al, 2022b) and so on.…”
Section: Triptolidementioning
confidence: 99%
“…For the malignant melanoma treatment, targeted delivery of triptolide was applied with cyclopeptide and αvβ3 integrin-specific exosomes ( Gu et al, 2022 ). Accumulating evidences revealed that triptolide has a strong antitumor effect in a broad range of cancers, including non-small cell lung cancer ( Zhou et al, 2022c ), colorectal cancer ( Liskova et al, 2022 ; Song et al, 2022 ), hepatocellular carcinoma ( Li et al, 2022b ), acute myeloid leukemia ( Chen et al, 2022b ; Kang et al, 2022b ) and so on.…”
Section: Natural Products Undergoing Clinical Evaluation In Pancreati...mentioning
confidence: 99%
“…Triptolide is a diterpenoid extracted from Tripterygium wilfordii Hook. f. which has a variety of biological activities such as antioxidation, immunomodulatory, and anticancer [ 183 , 184 , 185 ]. Some studies have shown that triptolide plays a significant role in the treatment of DKD, and a meta-analysis showed that triptolide significantly reduced albuminuria, blood urea nitrogen, serum creatinine, and urinary albumin/creatinine ratio in DKD animals [ 186 , 187 ].…”
Section: Natural Compoundsmentioning
confidence: 99%
“…Phosphoproteome and proteome analyses and RNA-seq were performed as previously described (21,22). After adjudgment of proteome data, phosphoproteome data was used to compare the phosphorylation of protein in Aurora-A knockdown TPC1 cells with the control group.…”
Section: Multi-omics Analysismentioning
confidence: 99%